Microwave-Assisted Efficient Synthesis of Aryl Thioethers through C–H Functionalization of Arenes - Liu, Yi-Chen; Lee, Chin-Fa (Synlett, 2013)
Microwave-assisted iridium-catalyzed meta C–H borylation followed by copper-promoted C–S bond coupling reactions in one pot is reported. This approach enables the syntheses of aryl thioethers in short reaction times (within 2.5 hours). The system shows good functional-group compatibility, as chloro, trifluoromethyl, fluoro, and pyridine groups are tolerated by the reaction conditions. Both aryl and alkyl thiols are coupled smoothly. The products were formed with excellent regioselectivity in meta position.
Keywords: microwave; aryl thioether; iridium; copper; C–H functionalization; arene